Kampanye Public Relations sebagai Upaya Meningkatkan Awareness Moderasi Beragama - Alifa Nur Fitri (UIN Antasari Banjarmasin, 2023)
The high level of intolerance among students is a concern, one in three students has an intolerant attitude. The form of intolerance is by agreeing to jihad and suicide. One of the efforts made by the Ministry of Religion is to conduct a Religious Moderation Campaign. UIN Walisongo as a moderate campus invites its students to have an attitude of moderation. The purpose of this study is to look at the planning stages of a public relations campaign carried out by students to campaign for religious moderation, whether it is effective in forming an attitude of religious moderation. The research methodology is qualitative research with case study analysis by observing religious public relations moderation campaigns. Collecting data by interview, observation and documentation. The results of this study indicate that students have carried out religious moderation campaigns well and used the campaign public relations planning stages by optimizing the use of Instagram social media, according to the media most accessed by students. The weakness of the moderation campaign that has been carried out is that it is not optimal in measuring awareness regarding religious moderation. However, students are able to convey messages well through Instagram media and get good insight among students